2D Non‐Van Der Waals Transition‐Metal Chalcogenide Layers Derived from Vanadium‐Based MAX Phase for Ultrafast Zinc Storage. Issue 27 (9th June 2022) - Du, Zhiguo; Gu, Jianan; Cao, Zhenjiang; Wang, Haiyang; Zhao, Qi; Ye, Yuxuan; Li, Bin; Chen, Weihua; Liu, Chuntai; Yang, Shubin
Abstract: Although 2D non‐van der Waals (vdW) layers show many intriguing physical and chemical properties as well as wide applications in the fields of electronics, catalysis, and energy storage, they still lack efficient synthetic approaches owing to their three‐dimensionally bonded structures. Here, a facile approach to produce 2D non‐vdW transition‐metal chalcogenide (TMC) layers based on the conversion of vanadium‐based MAX phase (V2 GeC) at high temperatures in hydrogen sulfide gas is developed. Associated with the etching of the germanium layers from the MAX phase, the vanadium layers are transformed into 2D non‐vdW V3 S4 layers. This originates from the self‐intercalation of ordered V atoms within the vdW space of intermediated vdW vanadium disulfide layers during the conversion reaction. Owing to the ultrathin character, highly exposed active surface, and unique vacancy‐enriched structure, the resultant 2D non‐vdW V3 S4 layers deliver a high reversible capacity of 341 mAh g −1, good rate capabilities, and long‐term cycling performance for zinc storage. Abstract : An efficient approach is developed to produce 2D non‐van der Waals (vdW) transition‐metal chalcogenide (TMC) (V3 S4 ) layers by topological conversion of vanadium‐based MAX phase. By harnessing the unique topological conversion, 2D non‐vdW ultrathin layers with vacancy‐enriched structure, and high electrical conductivity are achieved, exhibiting good electrochemical performance for zinc storage. The protocol can also produce a large number of non‐vdW TMC layers.